'We all belonged in there somewhere': young people's and carers' experiences of a residential sibling contact event. (July 2018) - Parker, Pamela; McLaven, Gracie
There is little research into planning for separated siblings in care even though in the UK approximately 75% of such children have lived apart from a brother or sister. Most contact arrangements comprise time-restrained meetings, often in contact centres and observed by social workers. This article discusses caregivers' and young people's experiences of a novel approach to sibling contact, Siblings Forever, an event devised to overcome some of the tensions and frustrations in usual arrangements. It involves a residential weekend when brothers and sisters living apart come together along with their kinship and foster carers. Interviews with six participating young people and six of their caregivers were analysed thematically. Five dominant themes were identified which encompassed young people's views on the occasion and their perceptions of differences from typical contact arrangements. They highlighted its unique atmosphere, the importance of having 'normal' experiences with their siblings, how old dynamics affected current interactions, caregivers' commitment to sustaining sibling relationships and the effort required to make the project work. The findings are discussed in the context of relevant theory and systemic concepts, and the pros and cons of managing sibling contacts in this way are identified.